"Click" Silica‐Supported Sulfonic Acid Catalysts with Variable Acid Strength and Surface Polarity. Issue 27 (5th April 2019) - Kasinathan, Palraj; Lang, Charlotte; Radhakrishnan, Sambhu; Schnee, Josefine; D'Haese, Cécile; Breynaert, Eric; Martens, Johan A.; Gaigneaux, Eric M.; Jonas, Alain M.; Fernandes, Antony E.
Abstract: Solid acid catalysts are central in our chemical industry and are major players in the valorization of bioresources. However, there is still a need to develop solid acid catalysts with enhanced acid strength and improved, or tunable, physicochemical profile to enhance the efficiency and sustainability of chemical processes. Here, a modular approach to tune the acid strength and surface polarity of silica‐supported sulfonic acid catalysts, based on a versatile copper‐catalyzed azide–alkyne cycloaddition (CuAAC)‐based anchoring scheme, is presented. The CuAAC‐formed triazole link was used to enhance the activity of the grafted sulfonic acids and to pair the acid sites with secondary hydrophobic functions. The beneficial effects of both the triazolium link and the paired hydrophobic site, as well as the optimal positioning of the sulfonic moiety on the triazole ring, are discussed in model esterification reactions. Abstract : How do you like your catalyst? An efficient and modular method is presented for the preparation of silica‐supported sulfonic acid catalysts, which further allows for the tuning of both their acid strength and surface polarity. The critical effects of these two parameters are presented on model esterification reactions.